Strategi Komunikasi Radio Odan dalam Menarik Minat Masyarakat sebagai Pendengar di Kabupaten Batubara Kecamatan Lima Puluh Pesisir: Tsaniatul Jannah - Tsaniatul Jannah (JISOSEPOL: Jurnal Ilmu Sosial Ekonomi dan Politik, 2024)
In this study, the researcher addresses the title "Communication Strategy of Radio Odan in Attracting Public Interest as Listeners in Batubara District, Lima Puluh Pesisir Sub-district". The primary objective of this study is to determine the communication strategies employed by Radio Odan to attract public interest as listeners in the districts of Batubara and Lima Puluh Pesisir. Furthermore, this study aims to identify and analyze the challenges faced by Radio Odan in its efforts to engage the public as listeners. This study used a qualitative descriptive approach, utilizing research informants including Zulfan Suri, ST, the Head of Odan Radio Station, and Hendra Gunawan, the radio broadcaster of Odan Subdistrict in Lima Puluh Pesisir District, Batubara Regency. The research findings indicate that the communication strategy of Radio Odan in attracting public interest as listeners in the Batubara District, Lima Puluh Pesisir Sub-district, is divided into two: the On Air communication strategy of Radio Odan and the Off Air communication strategy of Radio Odan. Radio Odan faces the challenge of attracting the interest of the community as listeners in the Batubara District, namely in the Lima Puluh Pesisir sub-district, due to the difficulty in capturing the interest of listeners among teenagers, specifically those under the age of 30